Case Report : Anterior Component Separation in Ventral Hernia : Short Term Outcome - Nasrul Haidi; Afif Ananta (Lembaga Pengembangan Kinerja Dosen, 2025)
Abdominal wall defects are a common surgical presentation and an indication for surgery worldwide, with an estimated prevalence of around 5% in the general population. Ventral hernias may be asymptomatic, but symptoms of discomfort and pain can significantly impact quality of life and may be associated with a negative body image. This technique utilizes the layered anatomy of the abdominal wall, and depending on which layer is released, it can be categorized as anterior component separation. This case study discusses a patient with a ventral hernia. After taking the patient's history, conducting a physical examination, and additional assessments, the patient underwent surgical intervention using the anterior component separation technique with mesh reinforcement. In this case study, the short-term outcomes (<2 years) for the post-operative hernia patient with anterior component separation will be evaluated. The study results indicate that the patient experienced mild to moderate post-operative pain, with no serious complications such as seroma or mesh erosion occurring, confirming that the choice of surgical technique and appropriate mesh selection can minimize the risk of infection and complications. The evaluation results show a significant improvement in the patient’s quality of life post-surgery, as the patient not only experienced pain reduction but also improvements in daily activities and satisfaction with the aesthetic results of their abdomen.